Extracellular vesicles from pancreatic ductal adenocarcinoma endoscopic ultrasound‐fine needle aspiration samples contain a protein barcode. (5th October 2021) - Inoue, Hiroyuki; Eguchi, Akiko; Kobayashi, Yoshinao; Usugi, Eri; Yamada, Reiko; Tsuboi, Junya; Akuta, Teruo; Horiki, Noriyuki; Iwasa, Motoh; Takei, Yoshiyuki
Abstract: Background: The survival rate of pancreatic ductal adenocarcinoma (PDAC) is very poor because early detection is difficult. Extracellular vesicles (EVs) are released from cells associating with the cellular condition and circulated in the blood. We aimed to identify EV proteins from endoscopic ultrasound‐fine needle aspiration (EUS‐FNA) biopsy samples in order to develop novel biomarkers for PDAC. Methods: Extracellular vesicles were isolated from EUS‐FNA samples of 40 PDAC patients and six autoimmune pancreatitis (AIP) patients to be used as a control. EV proteins were identified using nanoLC‐MS/MS. Results: Intact EVs approximately 200 nm in diameter were detected from EUS‐FNA samples. We identified 2059 or 1032 EV proteins in PDAC or AIP, respectively, and 1071 EV proteins were detected only in PDAC. One hundred and fifty‐three EV proteins were significantly different between PDAC and AIP: 64 proteins were down‐regulated in PDAC whereas 89 EV proteins were up‐regulated in PDAC including mucins, keratins, Ras‐related proteins, and olfactomedin‐4, which proteins have been reported to be elevated in PDAC tissue/blood, or cultured pancreatic cancer cell lines. Notably, in the 89 up‐regulated PDAC EV proteins we identified novel proteins including ADP‐ribosylation factor 3, CD55, pyruvate kinase, and lipopolysaccharide‐induced tumor necrosis factor. Out of 89 proteins, a total of 13 proteins including Ras‐related proteins were significantly elevated in PDAC stages II‐IV compared to PDAC stage I, including Ras‐related proteins, moesin, and CD55. Conclusions: The EV proteins obtained from EUS‐FNA samples contain a PDAC‐specific protein barcode. The EV proteins identified from EUS‐FNA samples include promising biomarkers for the diagnosis and clinical staging of PDAC. Abstract : Highlight Inoue and colleagues isolated extracellular vesicles from endoscopic ultrasound‐fine needle aspiration samples of patients with pancreatic ductal adenocarcinoma and, as controls, patients with autoimmune pancreatitis. Proteomic analysis of the extracellular vesicles revealed a pancreatic ductal adenocarcinoma‐specific protein barcode, representing promising biomarkers for the diagnosis and clinical staging of this disease.